Management Accounting Practices in the Era of Industry 4.0: Challenges and Opportunities for Business Innovation in Uzbekistan - Juraeva Mukhammadovna (PT. BATARI EDU CALYA, 2025)
The advent of Industry 4.0 has fundamentally transformed management accounting practices globally, presenting both unprecedented challenges and opportunities for business innovation. This study examines the current state of management accounting practices in Uzbekistan within the context of digital transformation, analyzing the challenges faced by organizations and identifying opportunities for innovation. Utilizing a mixed-methods approach combining quantitative surveys and qualitative case studies, this research investigates how Uzbek enterprises are adapting their cost management systems, performance measurement frameworks, and decision-support mechanisms to align with Industry 4.0 requirements. The findings reveal that while Uzbekistan has made significant strides through initiatives such as the